Westernization and preservation: an appropriated edutourism application as educational media for archaeological sites in Bedulu, Bali - Putu Sabda Jayendra; Gusti Ayu Dessy Sugiharni; Gusti Ngurah Yoga Semadi (International Journal of Advances in Applied Sciences, 2026)
The commercialization of tourism developing in West Bali poses risks that can damage the cultural identity not only of the island but, more crucially, of archaeological sites of cultural value. This research aims to develop a glocal educational tourism application for the Bedulu archaeological sites that offers a cultural alternative to the homogenization of the island's tourism culture. The novelty of this research lies in the combination of integrated digital storytelling for social media (IDSM) and advanced interactive digital storytelling (A-IDS), with a design approach that eliminates colonization and is community-centered. Using the Borg and Gall model, which is limited to the planning stage, data for this research were collected through literature review, field observation, surveys of 30 subjects, and semi-structured interviews with 5 purposively selected key informants (site managers, archaeologists, and user interface (UI)/user experience (UX) designers), as well as community co-design workshops. This research resulted in a cultural content map and a prototype application, which is the first in the world, and serves as an operational glocalization model, the first in the world to become a model for intergenerational educational digital heritage literature, for inclusive community development, and sustainable Balinese cultural heritage.